Aktivitas Buah Pare (Momordica charantia L.) sebagai Herbal Anti Hiperglikemia pada Kondisi Diabetes Melitus: Literature Review: AKTIVITAS BUAH PARE (Momordica charantia L.) SEBAGAI HERBAL ANTI HIPERGLIKEMIA PADA KONDISI DIABETES MELITUS: LITERATURE REVIEW - Kusuma, Ikhwan Yuda; Yuli Maesaroh, Yuli (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
Diabetes mellitus (DM) is a metabolic disorder characterized by high blood glucose (hyperglycemia) and impaired carbohydrate, fat, and protein metabolism due to effects on insulin secretion and insulin sensitivity. Oral antidiabetic is one of the therapeutic options to control blood glucose although its use has the potential for side effects and is very detrimental, especially in long-term use. Complementary therapies made from herbs such as bitter melon (Momordica charantia L.) are potential aspects to be alternative therapies because of the potential for lower side effects and affordable costs. This study describes the activity of bitter melon (Momordica charantia L.) as an antihyperglycemic agent. This type of research is a literature review which is described descriptively. The literature search method uses international and national journals conducted by online and identified using electronic databases from PubMed, Science Direct and Google Scholar. The data collection process uses the PICO (Population, Intervention, Compare, Outcome) approach. The results of this study showed that bitter melon (Momordica charantia L.) contains antidiabetic compounds including charantin and polypeptide-p. Bitter gourd, both in extract and non-extract form and in single or in combination, has been shown to reduce blood glucose levels, increase insulin sensitivity and levels, normalize HbA1c levels, improve lipid profiles and reduce oxidative stress. The conclusion of this study is that bitter melon has the potential as an antihyperglycemic herb in diabetic conditions.